Molecular mechanisms of Sar/Arf GTPases in vesicular trafficking in yeast and plants - Yorimitsu, Tomohiro; Sato, Ken; Takeuchi, Masaki (Frontiers in Plant Science, 2014)
Small GTPase proteins play essential roles in the regulation of vesicular trafficking systems in eukaryotic cells. Two types of small GTPases, secretion-associated Ras-related protein (Sar) and ADP-ribosylation factor (Arf), act in the biogenesis of transport vesicles. Sar/Arf GTPases function as molecular switches by cycling between active, GTP-bound and inactive, GDP-bound forms, catalyzed by guanine nucleotide exchange factors and GTPase-activating proteins, respectively. Activated Sar/Arf GTPases undergo a conformational change, exposing the N-terminal amphipathic α-helix for insertion into membranes. The process triggers the recruitment and assembly of coat proteins to the membranes, followed by coated vesicle formation and scission. In higher plants, Sar/Arf GTPases also play pivotal roles in maintaining the dynamic identity of organelles in the secretory pathway. Sar1 GTPase strictly controls anterograde transport from the endoplasmic reticulum (ER) through the recruitment of plant COPII coat components onto membranes. COPII vesicle transport is responsible for the organization of highly conserved polygonal ER networks. In contrast, Arf GTPases contribute to the regulation of multiple trafficking routes, including transport through the Golgi complex and endocytic transport. These transport systems have diversified in the plant kingdom independently and exhibit several plant-specific features with respect to Golgi organization, endocytic cycling, cell polarity and cytokinesis. The functional diversification of vesicular trafficking systems ensures the multicellular development of higher plants. This review focuses on the current knowledge of Sar/Arf GTPases, highlighting the molecular details of GTPase regulation in vesicle formation in yeast and advances in knowledge of the characteristics of vesicle trafficking in plants.